Perlindungan Hukum Pengguna Jasa Titip Beli Melalui Sosial Media Instagram - Ambaretha, Rosi (Jurist-Diction, 2024)
Abstract Standard agreements in the business of buying and selling services on Instagram are deemed insufficient to protect the rights of consumers who use their services. So that it raises criticism about how the legal relationship between business actors and consumers is in the purchase- trust service agreement through Instagram social media so that it can be seen what the characteristics of the deposit-purchase service agreement on Instagram actually are, and what is the form of liability for business actors in the deposit-purchase service agreement on Instagram. this. This study can be categorized as doctrinal research studies which uses a conceptual and statutes approach to answer and analyze the trust-purchase service agreement on Instagram. In fact, what are the characteristics of the agreement so that the form of accountability of business actors in this Instagram-purchase service agreement is what about the guidelines in the Civil Code and Laws. No. 8 of 1999 concerning Consumer Protection Law.   Keywords: Buy-entrust Service Agreement, Instagram social media, Law no. 8 of 1999, standard agreement   Abstrak perjanjian standart dalam usaha jasa titip beli di Instagram dirasa kurang cukup melindungi hak-hak konsumen pengguna jasanya. Sehingga memunculkan adanya kritikan mengenai bagaimana hubungan hukum pelaku usaha dan konsumen dalam perjanjian jasa titip beli melalui media sosial Instagram agar dapat diketahui seperti apa karakteristik perjanjian jasa titip beli di Instagram ini sebenarnya, serta bagaimana bentuk pertanggung gugtan pelaku usaha dalam perjanjian jasa titip beli di Instagram ini. Penelitian ini merupakan tipe penelitian hukum berjenis doctrinal research dan menggunakan pendekatan konseptual serta perundang-undangan untuk menjawab dan menganalisis perjanjian jasa titip beli di Instagram ini sebenarnya masuk kedalam karakteristik perjanjian apa sehingga bentuk tanggung gugat pelaku usaha dalam perjanjian jasa titip beli di Instagram ini bagaimana dengan perbedoman pada Kitab Undang-Undang Hukum Perdata dan Undang-Undang No.8 Tahun 1999 tentang Hukum Perlindungan Konsumen. Kata Kunci: Perjanjian Jasa titip Beli, media sosial Instagram, Undang – Undang No. 8 Tahun 1999, perjanjian baku